JENIS-JENIS JAMUR MAKROSKOPIS KELOMPOK DIVISIO BASIDIOMYCETES DI TAMAN HUTAN RAYA BUKIT BARISAN TONGKOH KABUPATEN KARO SUMATERA UTARA - David Sumanto Napitupulu; Paska Ramawati Situmorang (Elisabeth Health Jurnal, 2020)
Introduction: Mycology is one of subject Medical Laboratoty Tecnology Study Program..Some of students especially Medical Laboratory TechnologyStudy Program are not familiar with macroscopic fungi. So far, they know about macroscopic fungi from several sources such as:the internet and reserach journals. Add more, mushroom habitat in North Sumatera is very good for its growth, it is worth doing research to determine the types of macroscopic fungi that live and grow in it. Method:The researchmethod used isCruise method.There are two observation stations with 4 point route cruises. The fungal samples found were analyzed by descriptive method (Mueller et al., 2004). Fungal specimens are collected and identified in the field and laboratory. Basidiomycetes identification using several macroscopic fungal identification books like David Arora (1986) dan Simon & Schuster’s (1979)and thesis and journals on macroscopic fungi. Data analysis was done descriptively, the data from the identification results are tabulated and presented in tabular form. Result: Based on the results of research that has been done, obtained 49 types of macroscopic fungi that are included in the Basidiomycetes.Discussion: Macroscopic fungi usually found in hygrophyte habitats are the Basidiomycetes group of fungi. Basidiomycetes found were 5 orders, 17 families and 49 spesies. The most common species of fungi are members of the Order of Agaricales which consists of 29 species and the Order of Aphyllophorales of 15 species. This is because the Agaricales and Aphyllophorales groups have the ability to adapt well compared to other orders. The families that had the highest percentage of species were the Tricholomataceae and Polyporaceae families. This fungus is easy to find because it can grow in various habitats.